Effect of Allium cepa loaded polyacrylonitrile and polyvinyl pyrrolidone nanofibers on Candida albicans growth and the expression of CDR1 and CDR2 genes - Azam Nademi; Masoomeh Shams-Ghahfarokhi; Mehdi Razzaghi-Abyaneh (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: This study aimed to assess the effect of Allium cepa ethanolic extract (ACE) loaded polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP) nanofibers on Candida albicans (C. albicans) CDR1 and CDR2 genes expression.Materials and Methods: The minimum inhibitory concentrations (MICs) of ACE against C. albicans ATCC 10231 and clinical fluconazole (FLC)-resistant C. albicans PFCC 93-902 were determined using the Clinical and Laboratory Standards Institute (CLSI) protocol (M27-Ed4) at a concentration range of 45.3-5800 µg/ml. The nanofibers containing ACE (60 wt%) were fabricated using the electrospinning technique. The expression of the CDR1 and CDR2 genes was studied in the fungus exposed to ACE loaded nanofibers and 0.5×MIC concentration of FLC using the real-time polymerase chain reaction.Results: MIC50 and MIC90 of ACE against FLC-resistant C. albicans were 725 and 1450/mL, respectively. The expression of CDR1 (4.5-fold) and CDR2 (6.3-fold) were down-regulated after the exposure of FLC-resistant C. albicans to ACE-loaded nanofibers (P<0.05). Furthermore, the expression of CDR1 (2.8-fold) and CDR2 (3.2- fold) were up-regulated in FLC-treated C. albicans (P<0.05).Conclusion: The results revealed that nanofibers containing ACE interact with drug resistant genes expressed in C. albicans. Further studies are recommended to investigate the mode of action and other biological activities of ACE-loaded nanofibers against C. albicans and other pathogenic fungi